The Role of Stakeholders and Framework in Partnerships: The Management of the Collective Protected Zone in Indonesia - Subianto, Agus; Rianto, Budi; Bustami, Mohammad Reevany (Journal Public Policy, 2024)
This article reveals the experiences in Philippines, Ecuador, and West Papua-Indonesia, as well as the key contexts in East Java-Indonesia. The aim is to show that the management of a collective protected zone (CPZ) which is more appropriate in stakeholders’ partnership, sharing roles and responsibilities, and having a management framework for conservation for ecological, economic, social, and cultural purposes. It is in line with the dynamics of post-reform decentralization of marine resource management. This article discusses the decentralization policy toward partnerships between the village government and fisherman groups in managing CPZ Bangsring waters in Banyuwangi. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, documentation, and focus group discussion. The analysis reveals that the decentralization policy towards partnerships for the management of CPZ waters has succeeded in building partnership capacity to address collective action problems through the development of incentive structures and social capital. To develop community participation in ZPB, five initiatives are recommended (1) accommodating local cultural values (2) involving community groups and local institutions (3) using conservation areas according to the standards (3) government policies that ensure the sustainability of ZPB waters to be more collaborative and innovative.